2018
DOI: 10.1080/2162402x.2018.1510277
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p-CXCL14 axis related transcriptome profile and clinical outcome in diffuse gliomas

Abstract: GBM tissues are comprised of not only tumor cells but also tumor-associated nontumor cells, such as stromal cells and immune cells, which dilute the purity of glioma cells and function in glioma biology. However, the roles of miRNAs in modulating glioma purity are not clarified. In total, 838 glioma samples with transcriptome data, including 537 RNAseq data from TCGA project and 301 microarray data from Chinese Glioma Genome Atlas (CGGA project), were recruited into our investigation. Tumor purity, molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…We revealed that tumor purity was strongly associated with clinical and genomic characteristics. Low purity was an independent unfavorable prognostic indicator of OS in GC regardless of age and TNM stage, which consistent with the previous studies in other tumors 4,5,10 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We revealed that tumor purity was strongly associated with clinical and genomic characteristics. Low purity was an independent unfavorable prognostic indicator of OS in GC regardless of age and TNM stage, which consistent with the previous studies in other tumors 4,5,10 …”
Section: Discussionsupporting
confidence: 91%
“…Low purity was an independent unfavorable prognostic indicator of OS in GC regardless of age and TNM stage, which consistent with the previous studies in other tumors. 4,5,10 Genes with higher mutation rate in low-purity group were functionally annotated by DAVID. The most statistically significant annotation enrichments including protein kinase activity and activation of GTPase activity which may promote tumor growth and metastasis and partially explain the unfavorable prognosis in low-purity group.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical implications of our results, our findings about CXCL14 expression in glioma datasets support a view of CXCL14 tagging the most aggressive tumors (IV grade versus other grades), subtypes (mesenchymal and classical versus proneural), regions (leading edge of the tumors and infiltrating tumor areas), and G-CIMP status (NON G-CIMP vs G-CIMP). This last observation in particular may overlap with that, by Zeng and co-authors [31], about a trend of CXCL14 overexpression in IDH wt gliomas vs IDH mutant ones: G-CIMP tumors in fact were closely related to IDH mutation, and a better prognosis characterizes patients carrying them [26,34]. Moreover, G-CIMP subtypes are highly enriched among the proneural subtypes, compared with NON G-CIMP tumors [34].…”
Section: Discussionmentioning
confidence: 81%
“…The role of CXCL14 in cancer is controversial, as it was shown to play either tumor suppressive or tumor supportive roles, depending on the specific tumor type [13,27,28,29,30]. In glioblastoma, however, others and us showed that CXCL14 mRNA expression is enriched in tumor samples [17,31], where this chemokine is likely produced and secreted in the tumor microenvironment by reactive astrocytes [17] or other types of stromal cells [32]. To this regard, it is interesting to notice that, in the samples we tested in the present work, the most abundant expression of CXCL14 was found in cultured astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…CTSC was associated with proliferation of colorectal cancer cell [120], but this gene may be responsible for the proliferation of GBM cells. Genes such as ERBB2 [121], PDGFRA [122], PDGFRB [123], ITGA5 [124], AKT1 [125], COL1A1 [126], COL6A1 [127], THBS2 [128], PLOD2 [129], P4HA1 [130], IL10 [131], SPARC [132], IL18 [133], SRPX2 [134], CCL2 [135], PLAT [136], PLAU [137], CXCL12 [138], SFRP2 [139], ANGPT1 [140], CXCL14 [141], TGM2 [142], FSTL1 [143], IGFBP5 [144], IGFBP7 [145], LOX [146], and LOXL1 [147] were diagnosed with the development of GBM. ACTN1, COL4A5 , COL6A2 , LAMB2 , P3H1 , COL15A1 , COL16A1 , PCOLCE2 , PCOLCE , PCSK5 , IK3IP1, MFAP4 , FAM20C , C1QTNF1 , PLXNA3 , and NTNG1 were identified as novel biomarkers for the pathogenesis of GBM.…”
Section: Discussionmentioning
confidence: 99%